OP0226-HPR An In-Depth Process-Evaluation of a Goal Management Intervention Given by Rheumatology Nurses. (9th June 2015) - Arends, R.; Bode, C.; Taal, E.; van de Laar, M.
Abstract : Background: This study evaluated from a patient-perspective a holistic goal management intervention intended to support patients with polyarthritis in coping with their disease and its consequences. "Right on target" is a psychosocial group intervention, given by trained rheumatology nurses, that focuses on the threatened goals of patients. The new intervention is tailored to the needs and capacities of the individual participant. Objectives: The first aim of this study was to identify key components of the intervention from the perspective of patients who participated. The second aim was to evaluate whether the intervention was executed as intended (fidelity). Methods: A mixed-methods approach was applied to combine different perspectives. Both qualitative and quantitative analyses were applied to (i) written weekly evaluations from 85 participants and 4 trainers, (ii) 24 in-depth structured interviews with a random selection of participants post intervention, and (iii) audio recordings of 16 random sessions. Results: Participants experienced the aim of the intervention as improving adaptation to arthritis through stimulating flexible goal management behaviour. Participants highly valued that the intervention was provided in a group setting, and they perceived the group processes as increasing the effectiveness of the intervention. From patient perspective, the intervention achieved a higher awareness among participants of their personal goals, behavioural patterns, and possibilities and limitations caused by arthritis. Furthermore, change of behaviour (e.g. new behaviour) was noted by many participants. To a large extent, the applied behavioural change methods were perceived to contribute to the effectiveness of the intervention. With regard to the fidelity of the intervention, adherence to the protocol by the trainers was high. Differences were found with regard to the psychological communication skills of the trainers and the degree to which they were able to apply the intended coaching approach. The trainers had a vital role in facilitating the open and safe atmosphere that helped participants to share experiences and try out new behaviours. Conclusions: Participants identified group interaction, exercises, personal trajectory and the atmosphere as key components for achieving raised awareness and behavioural change. The possibility to shape the intervention to the needs, capacities and the social environment of individual participants was also highly valued. However, analysis of the intervention's fidelity indicated that both patients and nurses need support to benefit fully from the intervention's patient-expert approach. The training for nurses should include advanced psychological communication skills and nurses should be regularly supervised to reduce differences between trainers. References: Arends RY, Bode C, Taal E, van de Laar MAFJ (2013). A goal management intervention for polyarthritis patients: Rationale and design of a randomized controlled trial. BMC Musculoskeletal Disorders, 14:239 Disclosure of Interest: None declared